Pharmacokinetic interaction between tacrolimus and meropenem in pediatric kidney transplant patients - Brstilo, Lucas Joel (2023)
Introduction. Individualized therapy with tacrolimus is essential to ensure graft survival in patients with solid organ transplants. Tacrolimus is mainly metabolized by CYP3A4/5. The concomitant use of drugs possessing CYP3A4/5 modification activity may affect tacrolimus levels, impacting treatment effectiveness and safety.Objectives. To describe the incidence and characterize the interaction mechanism between tacrolimus and meropenem in pediatric kidney transplant patients. Methods. A longitudinal, observational, retrospective and prospective evaluation was developed in pediatric renal transplant patients treated with tacrolimus and meropenem. Dose-normalized tacrolimus trough concentrations (C0/D) were compared with and without meropenem. The Drug Interaction Probability Scale (DIPS) was performed to assess the probability of the drug interaction causation. Microsomes obtained from pediatric livers were genotyped for CYP3A5 polymorphisms and used for the in vitro drug-drug interaction study. Results. 26 patients aged 13.4 years (range: 3.1-18.0) were included of whom 10 (38.5%) presented the interaction which was classified as ‘probable’. In this subgroup of patients, the median (range) C0/D increased by 76.6% (range: 40.8-463.7) in presence of meropenem (p<0.01). An uncompetitive inhibition mechanism was observed in vitro. The maximum metabolism rate (Vmax) and the Michaelis-Menten constant (Km) of tacrolimus decreased in presence of meropenem by 56.9 and 34.8%, respectively. The intrinsic clearance of tacrolimus decreased by 34% in presence of meropenem in microsomes with CYP3A5*3/*3 genotype while no change was observed in microsomes with CYP3A5*1/*3 genotype. Conclusions. We report a novel interaction between tacrolimus and meropenem in pediatric kidney transplant patients and confirm the mechanism using human liver microsomes. Close monitoring of tacrolimus when co-administered with meropenem, particularly in patients with CYP3A5*3/*3 genotype, is recommended.